(untitled) - Einstein, Albert (New York, 1956)
Einstein’s essays share his philosophical beliefs, scientific reasoning, and hopes for a brighter future, and show how one of the greatest minds of all time fully engaged with the changing world around him.
Keywords: Nhà vật lý,Physicists; Tiểu sử,Biography